Place-based Guaranteed Minimum Income in Barcelona: (un)intended inclusionary policy for migrants - Laura Colini (European Journal of Spatial Development)
Discussions about Basic Income have gained traction recently when debating possible reforms of the welfare state, how to combat poverties and wealth inequalities, and to counteract job losses in the aftermath of the Pandemic. The role of cities engaging in various forms of basic income, such as the Guaranteed Minimum Income, and how they impact specific target groups as migrants and refugees, is still understudied. At the peak of the migration wave in Europe between 2015 and 2016, the European programme Urban Initiative Actions funded a pilot project on Basic Income led by the city of Barcelona. The scheme, called B-MINCOME, is meant to test the efficacy and effectiveness of combining a passive economic support of cash-transfer and active labour market policies geared toward their inclusion and re-insertion in the labour market. In particular, thanks to the inte-gration of local policies and the cooperation across departments, the project has impacted gender inequalities and indirectly helped the regularisation of undocumented migrants. Illustrating the Barcelona case study, the paper demonstrates that first, the approach adopted by B-MINCOME creates (unintended) benefits to migrants, second, that the combination of European and city level funds has fostered experimentation in terms of service design and provisions, and third, that local experimentations can further inform and challenge the design of public policies on inclusion at different scales.